Monitoring system for arthritis patients imaging approach - Viknesh (Nanyang Technological University, 2022)
The objective of this project is to develop a portable monitoring system to help grade arthritis within joints found in the hand. It uses a thermal array sensor to accumulate temperature values for joint specific regions. The thermal array data is displayed with the help of a single board computer, Raspberry Pi 4 (RP4). This data is then sent to a google sheet base to aggregate and store the data values. The stored temperature values are compared with real-time temperature values to see if the user’s joints are improving. This project also includes angle of flexion aggregation for the various multijointed system found in the hand, the study held was also expanded to single jointed systems. This data is also sent to a google sheet base to aggregate and store the data values. A comparison between stored flexion values and real-time flexion values concludes the joints state of measure. This dual method collates and feeds data into a cumulative sum average aggregation to further enhance the extracted features. All these data values are targeted towards a localized search engine, and displays the values collected according to user preference